Progressive nephritis, sensorineural hearing loss, and retinal abnormalities: a case of X-linked Alport syndrome with genetic confirmation - Islam, Mohammad Sirajul; Hossain, Ahmed; Bala, Chandra Shekhar; Islam, Md Ranaul; Sarker, Partha Sarothi; Islam, Md Dharul (Bangladesh Journal of Medicine, 2026)
Alport syndrome is a hereditary nephritis caused by mutations in the gene encoding type IV collagen, which presents with progressive kidney disease, sensorineural hearing loss, and eye abnormalities. We report a 20-year-old male who presented with acute kidney injury requiring hemodialysis, accompanied by progressive sensorineural hearing loss since age 8 and visual impairment requiring lens implantation. Family history revealed a deceased elder brother with renal failure. Clinical examination showed hypertension, bilateral pitting edema, bilateral sensorineural hearing loss, and ophthalmoscopic findings of pseudophakia, peripheral fleck retinopathy, and pale optic disc. Genetic analysis revealed a hemizygous COL4A5 c.1708G>C (p.Gly570Arg) mutation, classified as likely pathogenic according to ACMG guidelines.This case highlights the importance of comprehensive genetic testing in young patients with unexplained nephritis and its associated extra renal manifestations. Early diagnosis allows appropriate genetic counseling, family screening, and optimal therapeutic interventions including ACE inhibitors and renal replacement therapy. Bangladesh J Medicine 2026; 37(1): 68-71